Catalyst, preparation method and application thereof, and methanol synthesis method

By etching and neutralizing the aluminum-based metal organic frame, a catalyst with limited-domain copper-zinc active particles was prepared, which solved the problems of large particle size, low dispersion and poor hydrothermal stability in the existing catalysts, and achieved improvements in catalyst activity and thermal stability.

CN119897114AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311410672.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

In the existing methanol synthesis catalyst, the active component has large particle size and low dispersion, and the water stability and thermal stability of the metal organic frame support are poor.

Method used

By etching the aluminum-based metal organic frame, rich and evenly arranged alkaline sites are introduced to promote the neutralization reaction of copper and zinc, and an aluminum-based metal organic frame composite with limited domain copper and zinc active particles is obtained through drying and calcination.

Benefits of technology

The catalyst activity and thermal stability are improved, and copper-zinc active particles with smaller size and higher dispersion are obtained, which extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004518075030000141
    Figure BDA0004518075030000141
Patent Text Reader

Abstract

The invention relates to the technical field of alcohol synthesis, in particular to a catalyst, a preparation method and application thereof and a methanol synthesis method. The catalyst comprises a modified aluminum-based metal organic framework and active components copper oxide and zinc oxide loaded on the modified aluminum-based metal organic framework, and the modified aluminum-based metal organic framework is a product obtained by etching an aluminum-based metal organic framework. The preparation method of the catalyst comprises the following steps: (1) etching an aluminum-based metal organic framework by using a solution to obtain a product 1; (2) carrying out precipitation reaction on the product 1 and copper-zinc liquid to obtain a product 2; and (3) drying and roasting the product 2 to obtain the catalyst. When the catalyst disclosed by the invention is applied to a reaction for preparing methanol from synthesis gas, the catalyst has relatively high catalytic activity and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of methanol synthesis, and in particular to a catalyst and a preparation method and application thereof, as well as a method for synthesizing methanol. Background Art

[0002] Methanol is a basic product of carbon-based chemical industry and an organic chemical raw material. It is also a liquid clean fuel, easy to store and transport, and an important energy carrier. Methanol synthesis catalyst is a key factor in determining the effect of methanol synthesis reaction. At present, the most widely used methanol synthesis catalyst in industry is Cu-ZnO-Al2O3 catalyst. However, the traditional method of synthesizing Cu-ZnO-Al2O3 catalyst mostly adopts co-precipitation method. The difference in precipitation rates of different metals causes them to not precipitate simultaneously and evenly, thus affecting the dispersion and particle size of the metals. In severe cases, it will also lead to a decrease in catalytic activity and affect the service life of the catalyst.

[0003] Metal-organic frameworks are a new type of crystalline porous material. The coordination interaction between metal ions and organic ligands gives metal-organic frameworks a regular, rigid, and modifiable pore structure, which has the natural advantage of confining metal particles. However, the structure of most metal-organic frameworks will collapse and destroy rapidly in the aqueous phase; in addition, the thermal stability of most metal-organic frameworks is limited, and metal-organic ligand bond breaking will occur at temperatures above 200°C, which limits the application of metal-organic frameworks in the field of methanol synthesis catalysis. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of large particle size and low dispersion of active components in catalysts for methanol synthesis in the prior art, as well as poor water stability and thermal stability of metal organic framework carriers, and to provide a catalyst and a preparation method and application thereof, as well as a method for synthesizing methanol.

[0005] In order to achieve the above object, the first aspect of the present invention provides a catalyst, which comprises: a modified aluminum-based metal organic framework and active components copper oxide and zinc oxide supported on the modified aluminum-based metal organic framework;

[0006] Wherein, the modified aluminum-based metal-organic framework is a product obtained by etching the aluminum-based metal-organic framework.

[0007] A second aspect of the present invention provides a method for preparing a catalyst, wherein the method comprises:

[0008] (1) etching the aluminum-based metal organic framework with a solution to obtain product 1;

[0009] (2) subjecting the product 1 to a precipitation reaction with a copper-zinc solution to obtain a product 2;

[0010] (3) Drying and calcining the product 2 to obtain the catalyst.

[0011] The third aspect of the present invention provides a catalyst prepared by the method of the second aspect.

[0012] The fourth aspect of the present invention provides use of the catalyst described in the first aspect or the catalyst described in the third aspect in methanol synthesis.

[0013] A fifth aspect of the present invention provides a method for synthesizing methanol, wherein the method comprises:

[0014] (1) reducing the catalyst to obtain a reduced catalyst;

[0015] (2) reacting the synthesis gas in the presence of the reduced catalyst obtained in step (1) to obtain methanol;

[0016] Wherein, the catalyst is the catalyst described in the first aspect or the catalyst described in the third aspect.

[0017] Through the above technical scheme, the present invention etches a rigid aluminum-based metal-organic framework structure with excellent water stability and thermal stability, preferably using an alkaline solution for etching, to introduce abundant and evenly distributed alkaline sites into the metal-organic framework structure. The presence of these alkaline sites allows the neutralization reaction of copper and zinc to occur in situ in its pores, and then after calcination, an aluminum-based metal-organic framework composite material of confined copper-zinc active particles is obtained. The aluminum-based metal-organic framework composite material prepared by the present invention is subjected to X-ray diffraction testing and catalytic activity evaluation, and the results show that copper-zinc active particles with smaller size and higher dispersion that are adapted to the metal-organic framework pores can be obtained, and the confinement of the metal-organic framework pores also slows down the tendency of active particles to migrate and agglomerate under heat, thereby achieving the purpose of improving catalyst activity and thermal stability. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The specific implementation of the present invention is described in detail below in conjunction with the table. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0020] The first aspect of the present invention provides a catalyst, which comprises: a modified aluminum-based metal organic framework and active components copper oxide and zinc oxide supported on the modified aluminum-based metal organic framework;

[0021] Wherein, the modified aluminum-based metal-organic framework is a product obtained by etching the aluminum-based metal-organic framework.

[0022] According to the present invention, the aluminum-based metal-organic framework (Al-MOF) not only has a regular, rigid, and modifiable pore structure, but also can confine the active component particles when used as a carrier in the catalyst, affecting the particle size and dispersion of the active component copper-zinc oxide particles, thereby affecting the activity and thermal stability of the catalyst; secondly, the present invention introduces abundant and evenly distributed active sites into the structure of the aluminum-based metal-organic framework by etching the carrier, further improving the dispersion of the active component copper-zinc oxide particles, and confining the active component particles, slowing down the trend of thermal migration and agglomeration of active particles, thereby further improving the activity and thermal stability of the catalyst; in addition, the aluminum-based metal-organic framework of the present invention has excellent water stability and thermal stability, and its structure is not easy to collapse and destroy in the water phase. The structure of the metal-organic framework can also be maintained under temperature conditions above 200°C, expanding the application of the metal-organic framework in the field of methanol synthesis catalysis.

[0023] According to the present invention, in order to make the aluminum-based metal-organic framework have excellent water stability and thermal stability, make the catalyst suitable for use in aqueous solution and high temperature environment, improve the catalyst activity and thermal stability, and broaden the application field of the catalyst, preferably, the aluminum-based metal-organic framework is obtained by hydrothermal reaction of aluminum salt and ligand; specifically, the aluminum salt and the ligand are dissolved in a solvent, and a hydrothermal reaction is carried out at a certain temperature, wherein the solvent used for the hydrothermal reaction is not particularly limited, as long as the aluminum salt and the ligand can be dissolved, and the present invention preferably uses water as the solvent; preferably, after the hydrothermal reaction, it also includes the steps of washing and drying the solid particles obtained by the hydrothermal reaction.

[0024] Preferably, the pyrolysis temperature of the aluminum-based metal-organic framework is 400-500°C, more preferably 450-480°C.

[0025] Preferably, the temperature of the hydrothermal reaction is 100-200°C, and the time is 8-30 hours; further preferably, the temperature of the hydrothermal reaction is 120-170°C, and the time is 12-15 hours.

[0026] The aluminum salt is not particularly limited in the present invention, as long as it can be dissolved in the solvent used in the hydrothermal reaction. Preferably, the aluminum salt is selected from at least one of aluminum nitrate, aluminum carbonate, aluminum sulfate, aluminum chloride or aluminum isopropoxide;

[0027] Preferably, the ligand is selected from at least one of trimesic acid, terephthalic acid, and pyridinecarboxylic acid;

[0028] Preferably, the molar ratio of the aluminum salt to the ligand is 1-5, more preferably 1-3;

[0029] According to the present invention, in order to make the surface of the etched support better load the active component copper zinc oxide particles, preferably, the etching is to treat the aluminum-based metal organic framework with alkali;

[0030] Further preferably, the base is at least one of NaOH, Na2CO3, and NaHCO3.

[0031] According to the present invention, in order to increase the dispersion of copper-zinc particles, the active components of the catalyst, and the accessibility of active sites, and to enhance the activity and thermal stability of the catalyst, preferably, the average particle size of the copper oxide is 6-10 nm, and the average particle size of the zinc oxide is 3-6 nm.

[0032] More preferably, the average particle size of the copper oxide is 7-8 nm, and the average particle size of the zinc oxide is 4-5 nm.

[0033] According to the present invention, the molar ratio of copper to zinc in the active component is 1-10:1, more preferably 1-5:1.

[0034] According to the present invention, in order to better load the active ingredients of the catalyst on the aluminum-based metal-organic framework, slow down the thermal migration and agglomeration of the active particles, and prevent the reduction of catalyst activity and thermal stability, preferably, in the catalyst, the molar ratio of copper, zinc to aluminum in the aluminum-based metal-organic framework is 1:0.03-7.5, and more preferably 1:0.05-5.

[0035] In the present invention, the composition and structure of the catalyst can be measured by means of inductively coupled plasma spectroscopy (ICP), X-ray diffraction, etc., and can also be obtained by calculation based on the feed amount in a specific implementation.

[0036] The present invention has no particular limitation on the preparation method of the composite resin, as long as a catalyst having the above composition can be obtained. According to a preferred embodiment of the present invention, the second aspect of the present invention provides a method for preparing a catalyst, wherein the method comprises:

[0037] (1) etching the aluminum-based metal organic framework with a solution to obtain product 1;

[0038] (2) reacting the product 1 with a copper-zinc solution to obtain a product 2;

[0039] (3) Drying and calcining the product 2 to obtain the catalyst.

[0040] According to the present invention, the preparation method uses an alkaline solution to etch the aluminum-based metal-organic framework Al-MOF, introduces abundant and evenly distributed alkaline active sites into the metal-organic framework structure, and the presence of these alkaline active sites allows the reaction of preparing active components to occur in situ in the pores of the metal-organic framework, and then through drying and calcination, an aluminum-based metal-organic framework composite material of confined copper-zinc active particles is obtained; due to the confinement effect of the aluminum-based metal-organic framework Al-MOF active sites on the copper-zinc active particles, the copper-zinc active particles in the composite material are adapted to the pores of the metal-organic framework, and by regulating the acidity and alkalinity, concentration and etching time of the etching solution during the preparation process, the density and distribution of the introduced active sites are controlled, so that the prepared copper-zinc active particles have a smaller size and a higher dispersion, and can slow down the thermal migration and agglomeration of the active particles, thereby improving the activity and thermal stability of the catalyst.

[0041] According to the method provided by the present invention, the type and preparation of the aluminum-based metal organic framework Al-MOF can be the same as those described in the first aspect of the present invention, and the present invention will not be repeated here.

[0042] According to the preparation method of the present invention, in order to effectively etch the aluminum-based metal-organic framework Al-MOF, the introduced active sites can enable the copper-zinc salt to react in situ in the pores of the metal-organic framework. Preferably, in step (1), the solution is an alkaline solution, more preferably a NaOH, Na2CO3 or NaHCO3 solution.

[0043] According to the preparation method of the present invention, in order to control the density and distribution of active sites introduced by etching in the structural pores of the metal organic framework so that the prepared copper zinc active particles have a smaller size and a higher dispersion, preferably, in step (1), the concentration of the alkaline solution is 1-10 mol / L, preferably 1-5 mol / L.

[0044] Preferably, in step (1), the etching temperature is 20-200° C. and the etching time is 12-60 h. More preferably, the etching temperature is 25-150° C. and the etching time is 12-48 h.

[0045] According to the preparation method of the present invention, in order to make the copper-zinc solution and the precipitant react better in situ in the structural pores of the metal organic framework, so that the prepared copper-zinc active particles have a smaller size and a higher dispersion, and improve the activity and thermal stability of the catalyst, preferably, in step (2), the copper-zinc solution contains a copper compound and a zinc compound; further preferably, the copper compound is selected from at least one of copper nitrate, copper chloride, and copper sulfate, and the zinc compound is selected from at least one of zinc nitrate, zinc chloride, and zinc sulfate.

[0046] According to the preparation method of the present invention, in order to make the prepared catalyst have higher activity in methanol synthesis, preferably, in step (2), in the copper-zinc solution, the molar ratio of the copper compound to the zinc compound is 1-10:1, and further preferably, the molar ratio of the copper compound to the zinc compound is 1-5:1.

[0047] According to the preparation method of the present invention, in order to promote the in-situ reaction in the pores of the metal organic framework structure, preferably, in step (2), the reaction temperature is 20-80°C, the time is 10-80min, and the pH of the reaction system is 4-10. Further preferably, the reaction temperature is 25-60°C, the time is 15-60min, and the pH of the reaction system is 5-9.

[0048] According to the preparation method of the present invention, in order to better load the prepared catalyst active components on the aluminum-based metal-organic framework Al-MOF, slow down the thermal migration and agglomeration of active particles, and prevent the reduction of catalyst activity and thermal stability, preferably, in step (2), the molar ratio of copper and zinc in the copper-zinc oxide particles to aluminum in the aluminum-based metal-organic framework Al-MOF is 1:0.03-7.5, and more preferably 1:0.05-5.

[0049] According to the preparation method of the present invention, in order to make the prepared catalyst have higher catalytic activity and thermal stability, preferably, in step (3), the drying temperature is 60-150°C and the time is 5-24h; more preferably, the drying temperature is 80-120°C and the time is 6-12h.

[0050] Preferably, the calcination temperature is 200-600° C., and the time is 20-100 min; more preferably, the calcination temperature is 300-400° C., and the time is 30-60 min.

[0051] According to the technical solution of the present invention, by adjusting the acidity and alkalinity, concentration and etching time of the etching solution during the preparation process, the density and distribution of the introduced active sites are controlled, so that the obtained copper-zinc active particles can have an adjustable size and dispersion to adapt to different reaction conditions in the methanol synthesis process, expand the application field of the metal organic framework-supported copper-zinc catalyst obtained by the present invention, and save costs.

[0052] The third aspect of the present invention provides a catalyst prepared by the method of the second aspect.

[0053] The fourth aspect of the present invention provides use of the catalyst described in the first aspect or the catalyst described in the third aspect in methanol synthesis.

[0054] A fifth aspect of the present invention provides a method for synthesizing methanol, wherein the method comprises:

[0055] (1) reducing the catalyst to obtain a reduced catalyst;

[0056] (2) reacting the synthesis gas in the presence of the reduced catalyst obtained in step (1) to obtain methanol;

[0057] Wherein, the catalyst is the catalyst described in the first aspect or the catalyst described in the third aspect.

[0058] According to the method for synthesizing methanol of the present invention, preferably, in step (1), the reduction process is: in a mixed atmosphere containing hydrogen and nitrogen, at normal pressure, at 5-20°C·h -1 The temperature is raised to 200-300°C at a rate of 100°C and maintained for 5-10 hours.

[0059] Further preferably, in the mixed atmosphere, the volume ratio of hydrogen to nitrogen is 5-10:90-95.

[0060] According to the method for synthesizing methanol of the present invention, preferably, in step (2), based on the total volume of the synthesis gas, the content of CO in the synthesis gas is 13-15% by volume, the content of CO2 is 3-5% by volume, the content of hydrogen is 55-65% by volume, and the content of nitrogen is 15-29% by volume.

[0061] Preferably, the reaction temperature is 200-300° C., the pressure is 3-8 MPa, and the reaction time is 5-15 h.

[0062] The present invention will be described in detail below through examples.

[0063] Example 1

[0064] (1) Preparation of aluminum-based metal organic framework: 3.75 g of aluminum nitrate nonahydrate and 2.10 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal organic framework Al-MOF-I;

[0065] Etching of aluminum-based metal organic framework: 1.00 g of aluminum-based metal organic framework Al-MOF-I was immersed in 20 mL of 1 M NaOH solution, etched at 25 °C for 12 h, and washed with deionized water to obtain product 1;

[0066] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaOH to the suspension of product 1 at 25° C. in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal-organic framework) is 10:10:1. After aging for 30 minutes, the precipitation end point is when the pH reaches 5, and the suspension is washed with deionized water to obtain product 2;

[0067] (3) The product 2 was dried at 80°C for 6 hours and then calcined at 300°C in air atmosphere for 30 minutes to obtain catalyst 1.

[0068] The aluminum-based metal-organic framework Al-MOF-I obtained in step (1) was subjected to thermogravimetric measurement, and it was found that the thermal decomposition temperature of the aluminum-based metal-organic framework Al-MOF-I was 500°C.

[0069] Example 2

[0070] (1) Preparation of aluminum-based metal-organic framework: 2.04 g of aluminum isopropoxide and 2.10 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal-organic framework Al-MOF-II.

[0071] Etching of aluminum-based metal-organic framework: 1.00 g of aluminum-based metal-organic framework Al-MOF-II was immersed in 20 mL of 1 M NaOH solution, etched at 25° C. for 12 h, and washed with deionized water to obtain product 1.

[0072] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaOH to the suspension of product 1 at 25° C. in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal-organic framework) is 10:10:1. After aging for 30 minutes, the precipitation end point is when the pH reaches 5, and the suspension is washed with deionized water to obtain product 2;

[0073] (3) The product 2 was dried at 80°C for 6 hours and then calcined at 300°C in air atmosphere for 30 minutes to obtain catalyst 2.

[0074] The aluminum-based metal-organic framework Al-MOF-II obtained in step (1) was subjected to thermogravimetric measurement, and the pyrolysis temperature of the aluminum-based metal-organic framework Al-MOF-II was found to be 450°C.

[0075] Example 3

[0076] (1) Preparation of aluminum-based metal-organic framework: 3.75 g of aluminum nitrate nonahydrate and 6.30 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal-organic framework Al-MOF-III.

[0077] Etching of aluminum-based metal-organic framework: 1.00 g of aluminum-based metal-organic framework Al-MOF-III was immersed in 20 mL of 1 M NaOH solution, etched at 25° C. for 12 h, and washed with deionized water to obtain product 1.

[0078] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaOH to the suspension of product 1 at 25° C. in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal-organic framework) is 10:10:1. After aging for 30 minutes, the precipitation end point is when the pH reaches 5, and the suspension is washed with deionized water to obtain product 2;

[0079] (3) The product 2 was dried at 80°C for 6 hours and then calcined at 300°C in air atmosphere for 30 minutes to obtain catalyst 3.

[0080] The aluminum-based metal-organic framework Al-MOF-III obtained in step (1) was subjected to thermogravimetric measurement, and it was found that the thermal decomposition temperature of the aluminum-based metal-organic framework Al-MOF-III was 400°C.

[0081] Example 4

[0082] (1) Preparation of aluminum-based metal-organic framework: 3.75 g of aluminum nitrate nonahydrate and 2.10 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal-organic framework Al-MOF-I.

[0083] Etching of aluminum-based metal-organic framework: 1.00 g of aluminum-based metal-organic framework Al-MOF-I was immersed in 20 mL of 1 M NaHCO3 solution, etched at 25°C for 12 h, and washed with deionized water to obtain product 1.

[0084] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaHCO3 to the suspension of product 1 at 25°C in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal-organic framework) is 10:10:1. After aging for 30 minutes, the precipitation end point is when the pH reaches 5, and the suspension is washed with deionized water to obtain product 2;

[0085] (3) The product 2 was dried at 80°C for 6 hours and then calcined at 300°C in air atmosphere for 30 minutes to obtain catalyst 4.

[0086] Example 5

[0087] (1) Preparation of aluminum-based metal-organic framework: 3.75 g of aluminum nitrate nonahydrate and 2.10 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal-organic framework Al-MOF-I.

[0088] Etching of aluminum-based metal-organic framework: 1.00 g of aluminum-based metal-organic framework Al-MOF-I was immersed in 20 mL of 5 M NaOH solution, etched at 150° C. for 48 h, and washed with deionized water to obtain product 1.

[0089] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaOH to the suspension of product 1 at 25° C. in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal-organic framework) is 10:10:1. After aging for 30 minutes, the precipitation end point is when the pH reaches 5, and the suspension is washed with deionized water to obtain product 2;

[0090] (3) The product 2 was dried at 80°C for 6 hours and then calcined at 300°C in air for 30 minutes to obtain catalyst 5.

[0091] Example 6

[0092] (1) Preparation of aluminum-based metal-organic framework: 3.75 g of aluminum nitrate nonahydrate and 2.10 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal-organic framework Al-MOF-I.

[0093] Etching of aluminum-based metal-organic framework: 1.00 g of aluminum-based metal-organic framework Al-MOF-I was immersed in 20 mL of 1 M NaOH solution, etched at 25°C for 12 h, and washed with deionized water to obtain product 1.

[0094] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaOH to the suspension of product 1 at 25° C. in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal organic framework) is 1:1:10. After aging for 30 minutes, the precipitation end point is when the pH reaches 5, and the suspension is washed with deionized water to obtain product 2;

[0095] (3) The product 2 was dried at 80°C for 6 hours and then calcined at 300°C in air atmosphere for 30 minutes to obtain catalyst 6.

[0096] Example 7

[0097] (1) Preparation of aluminum-based metal-organic framework: 3.75 g of aluminum nitrate nonahydrate and 2.10 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal-organic framework Al-MOF-I.

[0098] Etching of aluminum-based metal-organic framework: 1.00 g of aluminum-based metal-organic framework Al-MOF-I was immersed in 20 mL of 1 M NaOH solution, etched at 25°C for 12 h, and washed with deionized water to obtain product 1.

[0099] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaOH to the suspension of product 1 at 60° C. in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal-organic framework) is 10:10:1. After aging for 30 minutes, the precipitation end point is when the pH reaches 9, and the suspension is washed with deionized water to obtain product 2;

[0100] (3) The product 2 was dried at 80°C for 6 hours and then calcined at 300°C in air atmosphere for 30 minutes to obtain catalyst 7.

[0101] Example 8

[0102] (1) Preparation of aluminum-based metal-organic framework: 3.75 g of aluminum nitrate nonahydrate and 2.10 g of trimesic acid were dissolved in 160 mL of water, reacted at 150° C. for 24 h, washed with deionized water, and dried at 100° C. to obtain a solid particle aluminum-based metal-organic framework Al-MOF-I.

[0103] Etching of aluminum-based metal-organic framework: 1.00 g of aluminum-based metal-organic framework Al-MOF-I was immersed in 20 mL of 1 M NaOH solution, etched at 25°C for 12 h, and washed with deionized water to obtain product 1.

[0104] (2) adding copper-zinc solution prepared by copper nitrate and zinc nitrate and NaOH to the suspension of product 1 at 25° C. in parallel to carry out a neutralization precipitation reaction, wherein the molar ratio of copper, zinc and aluminum (based on the aluminum content in the aluminum-based metal-organic framework) is 10:10:1. After aging for 30 minutes, the precipitation end point is when the pH reaches 5, and the suspension is washed with deionized water to obtain product 2;

[0105] (3) The product 2 was dried at 120°C for 12 hours and then calcined at 400°C in air for 30 minutes to obtain catalyst 8.

[0106] Comparative Example 1

[0107] (1) 241.6 g of copper nitrate trihydrate, 297.5 g of zinc nitrate hexahydrate and 37.5 g of aluminum nitrate nonahydrate were dissolved in 1 L of water, and the mixed solution and 4300 mL of 1 M NaOH aqueous solution were simultaneously added to a continuous neutralization reactor through a metering pump, and the reaction was carried out at a temperature of 25° C. and a pH of 5.0 for 30 min, and the mixture was washed with deionized water to obtain an intermediate product;

[0108] (2) The intermediate product was dried in an oven at 80°C for 6 hours and then calcined in air at 300°C for 30 minutes to obtain Catalyst 9.

[0109] The catalysts prepared in the examples and comparative examples were subjected to X-ray diffraction tests, and the average particle sizes of the catalysts were shown in Table 1:

[0110] Table 1

[0111] index Average particle size of copper oxide (nm) Average particle size of zinc oxide (nm) Example 1 8.1 5.2 Example 2 7.6 4.3 Example 3 7.5 5.0 Example 4 7.0 4.2 Example 5 7.4 4.9 Example 6 7.1 4.8 Example 7 7.2 5.0 Example 8 7.9 5.1 Comparative Example 1 11.2 8.8

[0112] It can be seen from Table 1 that under the same other synthesis conditions, compared with Comparative Example 1, the average particle size of the active ions of the catalyst prepared in Example is smaller, and the smaller grain size means that the copper-zinc components have a higher dispersion and more accessible active sites in the structure, thereby improving the activity and thermal stability of the catalyst; in addition, the present invention controls the density and distribution of the introduced active sites by adjusting the acidity and alkalinity of the etching solution, the concentration and the etching time during the preparation process, so that the prepared copper-zinc active particles have an adjustable size and dispersion, so as to adapt to different reaction conditions in the methanol synthesis process, expand the application field of the metal organic framework-supported copper-zinc catalyst prepared by the present invention, and save costs.

[0113] Test Case

[0114] The catalysts prepared in the examples and comparative examples were applied to the synthesis of methanol. The activity of the catalysts was evaluated in a micro-fixed bed continuous flow reactor using synthesis gas as the raw material. The synthesis gas composition was: CO 13-15% by volume, CO2 3-5% by volume, H2 55-65% by volume, and the balance was N2. Before the reaction, the catalyst was placed in a H2 / N2 mixed gas containing 5% H2 at 20°C·h under normal pressure. -1 The temperature was raised to 250°C at a rate of 10000 h / min for reduction treatment, wherein the catalyst loading was 4 mL. -1 The catalytic reaction of methanol synthesis was carried out under the conditions of reaction pressure of 5.0 MPa and reaction temperature of 250°C, and the initial methanol yield was measured to evaluate the initial activity of the catalysts prepared in the examples and comparative examples. The test results are shown in Table 2.

[0115] After the catalyst was heat treated for 5 hours under the conditions of normal pressure and 400°C in a synthetic gas atmosphere, the above-mentioned activity test conditions were repeated, and the methanol yield was measured to evaluate the heat-resistant activity of the catalyst. The test results are shown in Table 2. (Initial methanol yield-methanol yield after heat treatment) / initial methanol yield*100% is the activity decay ratio after heat resistance. The activity decay ratio calculation results of the catalysts prepared in the embodiment and the comparative example are shown in Table 2:

[0116] Table 2

[0117]

[0118] It can be seen from Table 2 that, under the same other synthesis conditions, compared with Comparative Example 1, when the catalyst prepared in Example is used for methanol synthesis, the initial yield of methanol is higher; when the catalyst after heat treatment is used for methanol synthesis, the yield of methanol is still high; and compared with Comparative Example 1, the activity decay ratio of the catalyst prepared in Example after heat treatment is relatively small, indicating that the aluminum-based metal organic framework carrier in the catalyst prepared in Example has high thermal stability, and can have a certain confinement effect on the particles of the catalyst active component, which can inhibit the migration and agglomeration of the catalytically active particles during heat treatment, thereby improving the activity and thermal stability of the catalyst.

[0119] Comparing Example 1 with Example 3, under the condition that other catalyst preparation conditions are the same, the raw material ratio for preparing the aluminum-based metal organic framework carrier is changed, and it is found that: Example 3 increases the feed ratio of the ligand trimesic acid in the raw material, and the initial activity of the obtained catalyst is higher, but after heat treatment, the activity of the catalyst is lower than that in Example 1, and the activity decay ratio of heat treatment is also greater than the latter, indicating that the reduction of the aluminum content in the catalyst carrier is not conducive to the improvement of the thermal stability of the catalyst.

[0120] Comparing Example 1 with Example 4, when other catalyst preparation conditions are the same, the alkalinity of the solution used for etching the aluminum-based metal organic framework is changed, and it is found that: the initial activity of the catalyst obtained after etching the carrier with a weaker alkaline NaHCO3 solution is higher than the initial activity of the catalyst obtained after etching the carrier with a stronger alkaline NaOH solution, but after heat treatment, the activity of the former is lower than that of the latter, and the proportion of the heat treatment activity decay of the former is greater than that of the latter, indicating that after etching the carrier with a weaker alkaline solution, the confinement effect of the carrier on the catalytically active particles is smaller, and the thermal stability of the obtained catalyst is poor.

[0121] Comparing Example 1 with Example 5, when other catalyst preparation conditions are the same, the concentration of the solution used for etching the aluminum-based metal-organic framework and the etching time are changed, and it is found that: in Example 5, a relatively high concentration of NaOH (5M) solution is used to etch the carrier for a delayed time (48 hours) at a relatively high temperature (150°C), and the activity of the obtained catalyst is relatively high. However, after heat treatment, the activity of the catalyst is lower than that in Example 1, and the proportion of activity decay due to heat treatment is also greater than that of the latter, indicating that etching the aluminum-based metal-organic framework for a long time at a relatively high temperature with a relatively high concentration of a strong alkaline solution will destroy the regular and rigid pore structure of the metal-organic framework, reduce the confinement effect of the carrier on the catalytically active particles, and thus affect the thermal stability of the catalyst.

[0122] Comparing Example 1 with Example 6, when other catalyst preparation conditions are the same, the feed ratio of the carrier to the copper-zinc liquid is changed, and it is found that: the molar ratios of copper, zinc and aluminum in the catalyst prepared in Example 6 are relatively small, so the catalytic activity when applied to methanol synthesis is relatively low. However, the activity decay ratio of the catalyst after heat treatment is relatively small, indicating that when the carrier feed ratio is large, the confinement effect on the catalytically active particles is stronger, which is beneficial to improving the thermal stability of the catalyst.

[0123] Comparing Example 1 with Example 7, when other catalyst preparation conditions are the same, the temperature of the neutralization reaction between the copper-zinc solution and the alkali is changed, it is found that: the temperature of the neutralization reaction in Example 7 is higher, and the initial catalytic activity of the obtained catalyst is higher, but after heat treatment, the activity of the catalyst is lower than that in Example 1, and the proportion of activity decay due to heat treatment is also greater than that of the latter, indicating that a higher temperature of the neutralization reaction is not conducive to improving the thermal stability of the catalyst.

[0124] Comparing Example 1 with Example 8, when other catalyst preparation conditions are the same, the drying and calcination temperatures of the product after the neutralization reaction are changed. It is found that: the initial catalytic activity of the catalyst obtained by increasing the drying and calcination temperatures in Example 8 is higher, but after heat treatment, the activity of the catalyst is lower than that in Example 1, and the activity decay ratio of the heat treatment is also greater than that of the latter, indicating that the excessively high drying and calcination temperature causes the active particles to migrate too fast, which is not conducive to improving the thermal stability of the catalyst.

[0125] It can be seen from the above embodiments and comparative examples that the catalyst carrier of the present invention has excellent water stability and thermal stability, and has a confining effect on catalytically active particles, which can slow down the migration and agglomeration of catalytically active particles when heated, and improve the thermal stability of the catalyst; in addition, by utilizing the preparation method of the present invention, abundant and evenly distributed alkaline sites are introduced into the aluminum-based metal organic framework structure of the catalyst carrier by etching, and the presence of these alkaline sites allows the neutralization reaction of copper and zinc to occur in situ in its pores, and then after calcination, copper and zinc active particles with smaller size and higher dispersion that are adapted to the pores of the metal organic framework can be obtained, thereby improving the activity of the catalyst.

[0126] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst, characterized in that The catalyst comprises: a modified aluminum-based metal organic framework and active components copper oxide and zinc oxide supported on the modified aluminum-based metal organic framework; Wherein, the modified aluminum-based metal-organic framework is a product obtained by etching the aluminum-based metal-organic framework.

2. The catalyst according to claim 1, wherein The aluminum-based metal organic framework is prepared by hydrothermal reaction of aluminum salt and ligand; Preferably, the pyrolysis temperature of the aluminum-based metal-organic framework is 400-500°C; Preferably, the temperature of the hydrothermal reaction is 100-200°C and the time is 8-30h; Preferably, the aluminum salt is selected from at least one of aluminum nitrate, aluminum carbonate, aluminum sulfate, aluminum chloride or aluminum isopropoxide; Preferably, the ligand is selected from at least one of trimesic acid, terephthalic acid, and pyridinecarboxylic acid; Preferably, the molar ratio of the aluminum salt to the ligand is 1-5, more preferably 1-3; Preferably, the etching is treating the aluminum-based metal organic framework with alkali; Preferably, the base is at least one of NaOH, Na2CO3, and NaHCO3.

3. The catalyst according to claim 1, wherein The average particle size of the copper oxide is 6-10 nm, preferably 7-8 nm; And / or, the average particle size of the zinc oxide is 3-6 nm, preferably 4-5 nm; Preferably, in the active component, the molar ratio of copper to zinc is 1-10:1, more preferably 1-5:

1.

4. The catalyst according to any one of claims 1 to 3, wherein In the catalyst, the molar ratio of copper, zinc to aluminum in the aluminum-based metal organic framework is 1:0.03-7.5, preferably 1:0.05-5.

5. A method for preparing a catalyst, characterized in that: The method comprises: (1) etching the aluminum-based metal organic framework with a solution to obtain product 1; (2) subjecting the product 1 to a precipitation reaction with a copper-zinc solution to obtain a product 2; (3) Drying and calcining the product 2 to obtain the catalyst.

6. The method according to claim 5, wherein: In step (1), the solution is an alkaline solution, preferably a NaOH, Na2CO3 or NaHCO3 solution; Preferably, the concentration of the alkaline solution is 1-10 mol / L, preferably 1-5 mol / L; And / or, the etching temperature is 20-200° C., and the etching time is 10-60 h. Preferably, the etching temperature is 25-150° C., and the etching time is 12-48 h.

7. The method according to claim 5 or 6, wherein: In step (1), the aluminum-based metal organic framework is prepared by hydrothermal reaction of aluminum salt and ligand; Preferably, the pyrolysis temperature of the aluminum-based metal-organic framework is 400-500°C; Preferably, the temperature of the hydrothermal reaction is 100-200°C and the time is 8-30h; Preferably, the aluminum salt is selected from at least one of aluminum nitrate, aluminum carbonate, aluminum sulfate, aluminum chloride or aluminum isopropoxide; Preferably, the ligand is selected from at least one of trimesic acid, terephthalic acid, and pyridinecarboxylic acid; Preferably, the molar ratio of the aluminum salt to the ligand is 1-5, more preferably 1-3.

8. The method according to any one of claims 5 to 7, wherein: In step (2), the copper-zinc solution comprises a copper compound and a zinc compound; Preferably, the copper compound is selected from at least one of copper nitrate, copper chloride and copper sulfate, and the zinc compound is selected from at least one of zinc nitrate, zinc chloride and zinc sulfate; And / or, the molar ratio of the copper compound to the zinc compound is 1-10:1, more preferably 1-5:1; And / or, the reaction temperature is 20-80°C, the reaction time is 10-80 min, and the pH of the reaction system is 4-10; preferably, the reaction temperature is 25-60°C, the reaction time is 15-60 min, and the pH of the reaction system is 5-9.

9. The method according to any one of claims 5 to 8, wherein: In step (2), in the precipitation reaction, the molar ratio of copper, zinc and aluminum is 1:0.03-7.5, preferably 1:0.05-5.

10. The method according to any one of claims 5 to 9, wherein: In step (3), the drying temperature is 60-150° C. and the drying time is 5-24 h; Preferably, the drying temperature is 80-120°C and the drying time is 6-12h; And / or, the calcination temperature is 200-600°C and the calcination time is 20-100min; Preferably, the calcination temperature is 300-400° C. and the calcination time is 30-60 min.

11. A catalyst prepared by the method according to any one of claims 5 to 10.

12. Use of the catalyst according to any one of claims 1 to 4 and 11 in methanol synthesis.

13. A method for synthesizing methanol, characterized in that: The method comprises: (1) reducing the catalyst to obtain a reduced catalyst; (2) reacting the synthesis gas in the presence of the reduced catalyst obtained in step (1) to obtain methanol; Wherein, the catalyst is the catalyst described in any one of claims 1-4 and 11.

14. The method according to claim 13, wherein: In step (1), the reduction process is: in a mixed atmosphere containing hydrogen and nitrogen, at normal pressure, at 5-20°C·h -1 The temperature is raised to 200-300°C at a rate of 100°C and maintained for 5-10 hours; Preferably, in the mixed atmosphere, the volume ratio of hydrogen to nitrogen is 5-10:90-95.

15. The method according to claim 13 or 14, wherein: In step (2), based on the total volume of the synthesis gas, the content of CO in the synthesis gas is 13-15% by volume, the content of CO2 is 3-5% by volume, the content of hydrogen is 55-65% by volume, and the content of nitrogen is 15-29% by volume; And / or, the reaction temperature is 200-300°C, the pressure is 3-8MPa, and the time is 5-15h.

Citation Information

Patent Citations

  • Preparation method and application of derivative catalyst based on LDH fixed transition MOF

    CN108816234A

  • Nickel-based dehydrogenation catalyst with core-shell structure and preparation method of catalyst

    CN111760570A

  • Method for preparing filtering membrane based on metal organic framework material and capable of degrading formaldehyde at normal temperature

    CN112871214A

  • Preparation method of sec-butyl alcohol dehydrogenation MOF catalyst

    CN112892598A

  • Preparation method and application of defect type metal organic framework composite catalytic material

    CN113856761A